MORPHOSEMANTIC FEATURES OF MEMENUHI ‘MEET’ IN THE LIGHT VERB CONSTRUCTIONS OF INDONESIAN - Nugraha, Danang Satria (Masyarakat Linguistik Indonesia, 2024)
This study examines the morphosemantic features of Indonesian light verb constructions (LVCs) that utilize the light verb memenuhi. LVCs are a common linguistic feature in Indonesian, consisting of a light verb and a noun that gives the construction a specific meaning. Using a corpus-based approach, this study analyzed LVCs with memenuhi from the Indonesian - Leipzig Corpora Collection (ILCC). This analysis focused on the semantic and syntactic properties of these constructions. The findings indicate that memenuhi is crucial in assigning specific meanings to LVCs. This study identified, at least, four semantic patterns: (1) /memenuhi/ + noun denoting ‘requirements’ or ‘expectations’, (2) /memenuhi/ + noun denoting ‘goals’ or ‘objectives’, (3) /memenuhi/ + noun denoting ‘obligations’ or ‘duties’, and (4) /memenuhi/ + noun denoting ‘situations’ or ‘encounters’. The first semantic pattern can occur in constructions such as /memenuhi kriteria/ ‘meet a criterion’ (-occurrence: 89.100). The second semantic pattern can occur in constructions such as /memenuhi target/ ‘meet a target’ (-occurrence: 47.931). The third semantic pattern can also occur in constructions such as /memenuhi janji/ ‘fulfill a promise’ (-occurrence: 8.238). Lastly, the fourth semantic pattern can occur in constructions such as /memenuhi panggilan/ ‘answer the call’ (-occurrence: 69.672). Syntactically, LVCs with memenuhi exhibit a range of structures, including transitive, intransitive, and ditransitive constructions. Among these three structures, there are at least three thematic relationships that can be found, namely agent, patient, and beneficiary. This study contributes to a deeper understanding of the role of light verbs in shaping the meaning of LVCs in Indonesian.